Women’s preference for caesarean section: a systematic review and meta-analysis of observational studies - Mazzoni, Agustina (2011)
BACKGROUND: The striking increase in caesarean section rates in middle and high-income countries has been partly attributed to maternal request. We conducted a systematic review and meta-analysis of women’s preferences for caesarean section. OBJECTIVES: To review the published literature on women’s preferences for caesarean section. SEARCH STRATEGY: A systematic search of MEDLINE, EMBASE, LILACS and PsychINFO was performed. References of all included articles were examined. SELECTION CRITERIA: We included studies that quantitatively evaluated women’s preferences for caesarean section in any country. We excluded articles assessing health providers’ preferences and qualitative studies. DATA COLLECTION AND ANALYSIS: Two reviewers independently screened abstracts of all identified citations, selected potentially eligible studies, and assessed their full-text versions. We conducted a meta-analysis of proportions, and a meta-regression analysis to determine variables significantly associated with caesarean section preference. MAIN RESULTS: 38 studies were included (n= 19,403). The overall pooled preference for caesarean section was 15.6% (95% CI: 12.5–18.9). Higher preference for caesarean section was reported in women with a previous caesarean section versus women without a previous caesarean section (29.4% – 95% CI: 24.4 to 34.8 - versus 10.1% – 95% CI: 7.5 to 13.1), and those living in a middle-income country versus a high-income country (22.1% –95% CI: 17.6 to 26.9 -versus 11.8% – 95% CI: 8.9 to 15.1). CONCLUSIONS: Only a minority of women in a wide variety of countries expressed a preference for caesarean delivery. Further research is needed to better estimate the contribution of women’s demand to the rising caesarean section rates.